PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PADA SMA UNGGUL NEGERI 2 BOARDING SCHOOL KOTA BANDA ACEH - Cut Nurviza; Yusrizal .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
ABSTRACTorganizational culture and leadership of principal are two important factors that affecting teachers’ work performance.  this study aimed to find out the influence between organizational culture and leadership on principal and work performance of teacher in state senior high boarding school unggul negeri 2 banda aceh. this research uses quantitative approach with descriptive method. the data analysis technique to test hypothesis was  multiple correlation and multiple regression. the results indicaded that: (1) there is significant influence between organizational culture and teacher’ work performance that namely 13,54%. it meant that the success of organizational culture implementation could be viewed from increased responsibility, discipline and subservience to the rules and custom; (2) there was a significant  influence between the leadership of headmaster and teachers’ work performance, namely 11.70%. this showed that the leadership of the principal influenced the work performance of teachers in general and it could be concluded that the skill possessed by the principal included conceptual skills, relationship skills with subordinates and skills as well as the conducive attitude and behavior of leadership which was very influential on teacher work performance; and (3) there is a significant influence between organizational culture and principal’s leadership on teacher’ work performance namelys 20.70%. the work performance of teachers will increase if there are the condition of relationships and healthy communication among the components of the school because with the pattern of relationships and communication which are well and good will encourage someone to do a good job.keywords: organizational culture, ladership, and work performance of teacher’s